Cooked Adzuki Bean Reduces High-Fat Diet-Induced Body Weight Gain, Ameliorates Inflammation, and Modulates Intestinal Homeostasis in Mice - Zhao, Qingyu; Liu, Zhenyu; Zhu, Yiqing; Wang, Han; Dai, Zijian; Yang, Xuehao; Ren, Xin; Xue, Yong; Shen, Qun (Frontiers in Nutrition, 2022)
Adzuki bean is widely consumed in East Asia. Although the positive effects of its biologically active ingredients on obesity have been confirmed, the role of whole cooked adzuki bean in preventing obesity and the relationship between the effects and gut microbiota remain unclear. Mice were fed either a low-fat diet (LFD) or high-fat diet (HFD) with or without 15% cooked adzuki bean for 12 weeks. Cooked adzuki bean significantly inhibited weight gain and hepatic steatosis, reduced high levels of serum triacylglycerol (TG), alanine aminotransferase (ALT), and aspartate aminotransferase (AST), and alleviated systemic inflammation and metabolic endotoxemia in mice fed a HFD. Importantly, cooked adzuki bean regulated gut microbiota composition, decreased the abundance of lipopolysaccharide (LPS)-producing bacteria (Desulfovibrionaceae，Helicobacter，and Bilophila), and HFD-dependent taxa (Deferribacteraceae, Ruminiclostridium_9, Ruminiclostridium, Mucispirillum, Oscillibacter, Enterorhabdus, Tyzzerella, Anaerotruncus, Intestinimonas, unclassified_f_Ruminococcaceae, Ruminiclostridium 5, and Ruminococcaceae), and enriched Muribaculaceae, norank_f_Muribaculaceae, Anaeroplasma, Lachnospiraceae_NK4A136_group, and Lachnospiraceae to alleviate inflammation and metabolic disorders induced by HFD. These findings provide new evidence for understanding the anti-obesity effect of cooked adzuki bean.